Contrast-induced nephropathy following PCI: can we calculate a safe contrast volume?. (3rd October 2022) - Costa, H; Silva, M; Santo, M E; Mota, T; Fernandes, R; Palmeiro, H; Marto, S; Franco, P; Carvalho, D; Bispo, J; Guedes, J; Mimoso, J; et al.
Abstract: Introduction: Acute kidney injury (AKI) due to contrast induced nephropathy (CIN) is a common complication after percutaneous coronary intervention (PCI) in patients with acute coronary syndrome (ACS), and is associated with prolonged hospitalizations and elevated cardio and renovascular morbidity. Scientific evidence demonstrates that the mean volume of contrast (VolC) and ratio with creatinine clearance (CrCl) (VolC/CrCl) are independent predictors of CIN, but the accepted optimal value remains controversial. Objective: Population characterization. To evaluate whether the calculation of VolC using the VolC/ClCr ratio <3.7 used in our Cath lab during PCI of ACS allows preventing the development of AKI by CIN, and whether the development of early vs late AKI influences outcomes. Methods: Retrospective study between 2017/2020, composed of n=378 patients who suffered ACS. Descriptve analysis was carried out regarding the demographic and clinical characteristics of the patients. Chi-Square test was used for categorical variables and the T-Student test for numerical variables, with a significance level of 95%. Results: A total of 378 patients were identified, with a mean age of 64.5±11.2 years, 78.6% were male. 60.1% had hypertension, 48.4% dyslipidemia, 24.3% diabetes, 2.6% chronic renal failure (CRF) and 1.6% heart failure. Of these, 12.7% developed AKI (<24h in 1.9% vs ≥24h in 10, 8%). Indepedent prognostic factors for development of AKI were smokers (AKI ≥24h 7 (4.8%) vs AKI<24h 2 (1.4%), p=0.001), diabetes (AKI≥24h 17 (19%) vs AKI <24h 2 (2.2%), p=0.007), CRF (AKI ≥24h 6 (60%) vs AKI <24h 1 (10%), p=0.001), CrCl (AKI ≥24h 65.8±27.1, p=0.001), ratio VolC/CrCl (AKI ≥24h 3.3±2.5, p=0.001) and LVEF (AKI ≥24h 51.4±9.7, p=0.001). Mortality afected 4.2% of the patients, and was more frequente in AKI subjects (AKI ≥24h 7 (70%) vs AKI <24h 1 (10%), p=0.001). Using a ratio <3.7 allowed to prevent AK <24h but not AKI ≥24h (AKI <24h ratio <3.7 = 3 (1%) vs ratio ≥3.7 = 9 (4.1%), p=0.001) (AKI ≥24 ratio <3.7 = 30 (25%) vs ratio ≥3.7 = 11 (9.7%), p=0.001). A ratio <2.0 allowed to prevent both early and late AKI (AKI <24h ratio <2.0 = 0 (0%) vs ratio ≥2.0 = 7 (4.5%), p=0.001) (AKI ≥24 ratio <2.0 = 11 (5.6%) vs ratio ≥2.0 = 30 (19.1%), p=0.001). Conclusion: In patients submitted to ACS PCI, the development of AKI increases mortality, especial if AKI emerge after 24h. We report a more suitable ratio VolC/ClCr <2.0, that allow us to calculate a safe VolC that will help to prevent both early and late AKI in selected patients wtih ACS. Funding Acknowledgement: Type of funding sources: None.